Effects of Satellite Transmitters Fitted to Breeding Cory's Shearwaters - Villard, Pascal; Bonenfant, Christophe; Bretagnolle, Vincent (The Journal of wildlife management, 2011)
We studied the effects of a new technique to fix satellite transmitters on the feeding behavior and chick body growth of the Cory's shearwater (Calonectris diomeded). Transmitters did not significantly affect the breeding bird's body mass or diving performance. However, on average, pairs with ≥1 adult equipped with a transmitter brought a lighter meal (54.8 ± 18.9 g) to nestlings than did control birds or the same pair with the transmitter removed (77.4 ± 8.3 g) leading to a decreased chick body growth. However at fledging, chicks in control and treatment groups had similar body mass whether parents were equipped with a PTT or not. Our method of transmitter attachment could therefore be an appropriate alternative for studying the ecology of procellariiforms weighing < 1 kg given that birds are fitted with transmitters for <2 weeks and restricted to 1 parent only.